Teachers’ Perception Toward The Role Of Instructional Supervisor - Mochamad Alfan (Universitas Muhammadiyah Jember, 2022)
This Study examined the teacher’s perception toward the role of supervisor at Darussalam Boarding School Gontor Ponorogo East Java, Indonesia. This Study employs a quantitative methodology and using questionnaire in collecting data. Respondents were teachers of Darussalam Boarding School Gontor, the population was 300 teachers, stratified random sampling was employed to get sample because the population is homogenous in their dedication and varied in their characteristics. The study aim to assess teachers’ perception on the important of some supervisory task and examined teachers’ perceptions toward to which extent supervisors involved in the tasks. The finding indicate that supervisory tasks were regarded as important by teachers and were proven by the high percentages of teacher (68%-99%) who agreed to supervisory tasks. On the other hand, teachers regard on supervisor’s involvement toward the tasks was also positive. Another finding shows that supervisory activities also regarded as important by most teachers, the percentages of important assumption of teachers indicated in range 80%-99%,, in which evaluating the teaching-learning process become most important tasks of supervisor (99%), at the same time, teachers regard school supervisors very well involved in supervisory activities during teaching and learning process which was can be noticed from the high percentage of teachers’ responses toward each task. Teachers regard evaluating teaching and learning, advising and helping teachers in problem relating to teaching and learning are the tasks most often performed by school supervisors.